Implementasi Arsitektur Data Warehouse Dan Dashboard Business Intelligence Untuk Analisis Performa Penjualan Ritel Elektronik Di Myanmar Menggunakan Pentaho Dan Tableau - Taqiyuddin Ahmad Al Aufa; Adriano Femaz Rivaldy; Farel Ega Nurroyan; Muhammad Fawwaz Dhiaulhaq Hud; Amalia Anjani Arifiyanti (CV. SINAR HOWUHOWU, 2026)
This study aims to implement a Data Warehouse architecture and a Business Intelligence dashboard to analyze the electronic retail sales performance in Myanmar. Raw data sourced from the Electronic Retail Dataset (2020–2023) has high complexity and poor quality (dirty data). The methods used include building a data pipeline with PostgreSQL as a staging area, the Extract, Transform, Load (ETL) process using Pentaho Data Integration, Star Schema modeling, and interactive visualization using Tableau via a Virtual Datamart. The results show that the ETL process successfully cleaned data anomalies and produced an integrated schema. The resulting dashboard reveals strategic insights, such as the revenue dominance of